Hubungan job insecurity dan komitmen organisasi pada karyawan PT. KX - Markus, Viestar Jeffran; Jatmika, Devy (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2017)
An unstable condition of a company causes the need to downsize the organizations structure by doing layoff. This circumstance evokes a feeling of insecurity in the employees, known as job insecurity. The present study’s objective was to examine if there is a relationship between job insecurity and organizational commitment in the current employees of PT. KX in Jakarta, while other employees have been laid off. The present study was done by distributing a questionnaire to 89 employees in PT. KX. The study was a correlational research with quantitative method. The sampling technique was criterion sampling. The results showed that there is a significant negative relationship between job insecurity and organizational commitment. Therefore, the conclusion of the present study is that the lower the job insecurity among employees, the higher the organizational commitment towards the company, vice versa.